Network meta-analysis of first-line thrombectomy strategy for acute posterior circulation strokes: a preliminary evaluation for combined approach - Ye, Gengfan; Cao, Ruoyao; Chen, Pandi; Wang, Hongcai; Wang, Dongfeng; Chen, Maosong; Li, Zhenqiang (Frontiers in Neurology, 2023)
Objective Thrombectomy may provide superior results compared to best medical care for acute posterior circulation strokes (PCS). Contact aspiration (CA), stent retriever (SR), and combined SR + CA (SRA) are commonly employed as first-line techniques. However, the optimal strategy and the role of SRA remain uncertain. Methods Systematic searching was conducted in three databases (PubMed, Embase, and Cochrane). Network meta-analyzes were performed using random-effects models. The reperfusion and clinical outcomes were compared. Pooled outcomes were presented as odds ratios (OR) with 95% confidence intervals (CI). Rankograms with surface under the cumulative ranking curve (SUCRA) were calculated. Results Seventeen studies were included, involving a total of 645 patients who received first-line CA, 850 patients who received SR, and 166 patients who received SRA. Regarding final recanalization outcomes, both first-line SRA (OR = 3.2, 95%CI 1.4–11.0) and CA (OR = 2.1, 95%CI 1.3–3.7) demonstrated superiority over SR in achieving successful reperfusion [modified Thrombolysis In Cerebral Infarction (mTICI) 2b-3], with values of SUCRA 91.1, 58.5, and 0.4%, respectively. In addition, first-line SRA showed an advantage in achieving final mTICI 2c/3 compared to CA (OR = 3.6, 95%CI 0.99–16.0) and SR (OR = 6.4, 95%CI 1.3–35.0), with SUCRA value of 98.0, 44.7, and 7.2%, respectively. Regarding reperfusion outcome after the first pass, SRA also achieved a higher rate of mTICI 3 than SR (OR = 4.1, 95%CI 1.3–14.0), while CA did not (SUCRA 97.4, 4.6, 48.0%). In terms of safety outcomes, first-line CA was associated with a lower incidence of symptomatic intracranial hemorrhage (sICH) compared to SR (OR = 0.38, 95%CI 0.1–1.0), whereas the SRA technique did not (SUCRA 15.6, 78.6, 55.9%). Regarding clinical prognosis, first-line CA achieved a higher proportion of functional independence (modified Rankin Scale (mRS) 0–2) at 90 days than SR (OR = 1.4, 95%CI 1.1–1.9), whereas SRA did not (SUCRA 90.5, 17.4, 42.1%). Conclusion For acute PCS, a first-line CA strategy yielded better results in terms of final successful reperfusion and 90-day functional independence compared to SR. As the combined technique, first-line SRA was associated with superior first-pass and final reperfusion outcomes compared to SR. However, no significant difference was observed in functional independence achieved by first-line SRA compared to the other two strategies. Further high-quality studies are warranted.